2003
DOI: 10.1097/00001665-200301000-00019
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 Mutations among Thai Children with Crouzon and Apert Syndromes

Abstract: Crouzon and Apert syndromes have been reported to be associated with mutations in Fibroblast Growth Factor Receptor 2 (FGFR2) gene in various ethnic groups, but never in Southeast Asian subjects. Therefore, the authors conducted a study to characterize 11 Thai patients: four with Crouzon syndrome and seven with Apert syndrome. All cases are sporadic. Mean paternal and maternal ages were 38.7 and 28.6 years, respectively. Molecularly, all patients were found to have mutations in the FGFR2 gene. Three mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This mutation was detected in 1 of 9 Japanese cases of sporadic Crouzon syndrome (6), one sporadic Crouzon case in the report of Reardon et al (5), 2 of 30 German craniosynostosis patients (7), and one of 259 craniosynostosis patients in the United Kingdom (8), but there are no reports of the G1073A mutation in familial Crouzon syndrome or other types of craniofacial syndrome [H]. The high paternal age in the present case may be associated with de novo FGFR2 mutation as previously described (9).…”
Section: Discussionsupporting
confidence: 57%
“…This mutation was detected in 1 of 9 Japanese cases of sporadic Crouzon syndrome (6), one sporadic Crouzon case in the report of Reardon et al (5), 2 of 30 German craniosynostosis patients (7), and one of 259 craniosynostosis patients in the United Kingdom (8), but there are no reports of the G1073A mutation in familial Crouzon syndrome or other types of craniofacial syndrome [H]. The high paternal age in the present case may be associated with de novo FGFR2 mutation as previously described (9).…”
Section: Discussionsupporting
confidence: 57%
“…These outcomes must not be disregarded because continuously accumulating evidence strongly points to increased morbidity in the progeny of older fathers. For instance, rising paternal age has been correlated to a higher incidence of specific autosomal dominant disorders, such as neurofibromatosis type 1, several types of craniosynostosis (e.g., Apert, Crouzon, Pfeiffer, and Muenke syndromes), achondroplasia, retinoblastoma, and multiple endocrine neoplasia types 2A and 2B (38)(39)(40). This increased risk of specific ''paternal age effect'' conditions has been related to several mechanisms, such as a higher predisposition to random copy-error mutational events in the male germline, age-associated DNA damage resulting from accumulating oxidative stress and exogenous mutagenic agents, less effective DNA damage repair mechanisms, and the recently emerging hypothesis of selfish selection-the advantageous selection and clonal expression of improper, mutation-bearing spermatogonia (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…By use of a chi-squared two-tailed analysis, Frattarelli et al (12) found a statistically significant difference in blastocyst development on day 5 as the male population aged (P< .001), and the cutoff point seemed to be at >50 years. In the paternal age group %50 years, 40 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 339 340 341 342 343 344 345 346 347 348 349 350 351 352 353 354 statistical significance but noted that this may be related to the limited number of...…”
Section: Embryo Numbersmentioning
confidence: 99%
“…All mutations were associated with increased paternal age and molecularly proved to be a paternal origin of mutation. 66,67 Glaser et al 68 have found that two nucleotide substitutions in the human FGFR2 gene (C755G or C758G) are responsible for virtually all sporadic cases of Apert syndrome. This condition is 100-1000 times more common than that genomic mutation frequency data predict.…”
Section: Autosomal Dominant (Ad) Diseasesmentioning
confidence: 99%